PERAN MAJELIS PENGAWAS DAERAH DALAM PENGAWASAN TUGAS JABATAN NOTARIS DI KABUPATEN CILACAP - , Hastari Endah Rahayu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was aimed to know the monitoring enforcement conducted by Regional Watcher Council (MPD) related to obligations and prohibitions of Notary in Cilacap Regency and efforts that could be conducted to improve the authority enforcement of Regional Watcher Council (MPD) in Cilacap Regency. This was a juridical empirical research. Juridical meant that the writer conducted research form juridical aspects. Empirical meant that the writer conducted research by seeing reality occurred in a direct practice on Monitoring towards Notary Tasks Enforcement in Cilacap Regency. Data used was a secondary data in forms of primary, secondary and tertiary law materials and also a primary data in form of an interview with Regional Watcher Council and Notary of Cilacap Regency. From the research result it was known (1) the monitoring conducted by Regional Watcher Council(MPD) towards notary in Cilacap Regency covered preventive and repressive actions due to its area width and also its distance coverage so that the examination was conducted by gathering all notary in one place, the examination conducted was only formality in nature, (2) Issues Being Berriers Facing Local Supervision Council in Conducting Cupervision Against Notary Officials in the Cilacap District Regional The Extent of the area is supervised, the distance traveled is far, beside that there are also constraints in the forms of a lack of human resources, lack of funds, time constraints and lack of socialization.